Carbenoid-mediated N–O bond insertion and its application in the synthesis of pyridines - Qi, Xinxin (2013)
Highly efficient synthesis of 3-hydroxypyridines has been developed based on carbenoid-mediated N–O bond insertion. Treatment of δ-diazo oxime ethers with dirhodium complex Rh2(tfacam)4 rapidly provides a variety of pyridines in 5–10 minutes in good to excellent yields.